2018
DOI: 10.1038/s41598-018-26448-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel human microbe-disease associations inference based on network consistency projection

Abstract: Increasing evidence shows that microbes are closely related to various human diseases. Obtaining a comprehensive and detailed understanding of the relationships between microbes and diseases would not only be beneficial to disease prevention, diagnosis and prognosis, but also would lead to the discovery of new drugs. However, because of a lack of data, little effort has been made to predict novel microbe-disease associations. To date, few methods have been proposed to solve the problem. In this study, we devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…NCP was first proposed by Gu et al (2016) to predict miRNA-disease association. Zou et al (2018) used this method to predict the association between microorganisms and diseases and achieved good results. NCP is a method based on a general nonparametric network, which belongs to the category of unsupervised learning.…”
Section: Resultsmentioning
confidence: 99%
“…NCP was first proposed by Gu et al (2016) to predict miRNA-disease association. Zou et al (2018) used this method to predict the association between microorganisms and diseases and achieved good results. NCP is a method based on a general nonparametric network, which belongs to the category of unsupervised learning.…”
Section: Resultsmentioning
confidence: 99%
“…The Human Microbe Disease Association Database (HMDAD) was the first resource developed using literature mining to systematically gather experimental data to study microbe–disease associations (Ma et al, 2017b). Several tools have been developed thereafter to utilize the curated data from HMDAD and score human microbe associations using advanced mathematical approaches (Chen et al, 2017; Huang et al, 2017a; Huang et al, 2017b; Wang et al, 2017b; Peng et al, 2018; Zou et al, 2018; Qu et al, 2019). The above set of tools focuses on identifying associated genera across a set of selected diseases and is eventually used to find diseases having similar pattern of associated microbes.…”
Section: Introductionmentioning
confidence: 99%
“…Some similarity calculation methods of diseases have been proposed using different kinds of disease information. Symptom-based disease similarity has been increasingly demonstrated that it can provide effective information for MDA prediction ( Peng et al, 2018b ; Zou et al, 2018 ). In this work, we also introduced symptom-based disease similarity and utilized to represent the similarity matrix.…”
Section: Methodsmentioning
confidence: 99%